Reflections on a Career in Marine Geoscience - A. B. Watts (Perspectives of Earth and Space Scientists)
Abstract I began my career in the late 1960s at a time when some major oceanographic institutions were running upwards of 30 cruises a year. By the early 1980s, changes in funding patterns, satellite remote sensing, and “law of the sea” had started to impact ocean exploration. Nevertheless, technological advances, especially in sonar and seismic systems, have led to new discoveries on seafloor processes and underlying structures. Today, marine geoscience plays a pivotal role in Earth system science through projects such as Seabed 2030, International Ocean Drilling (IODP), and seismic imaging of mantle lithosphere, each of which pose opportunities and new challenges for the next generation.